Proceedings of the 5th International Conference on Vehicle Technology and Intelligent Transport Systems 2019
DOI: 10.5220/0007766900002179
|View full text |Cite
|
Sign up to set email alerts
|

Using an Intelligent Vision System for Obstacle Detection in Winter Condition

Abstract: This paper explores the performance of an Advanced Driving Assistance System (ADAS) during navigation in urban traffic and a winter condition. The selected ADAS technology, Mobileye, has been integrated into a hydrogen electric vehicle. A set of three cameras (visible spectrum) has also been installed to give a surrounding view of the test vehicle. The tests were carried out during the dusk as well as in the night in winter condition. Using Matlab, the messages provided by Mobileye system have been analyzed. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It supports the dramatic impact of winter on object detection. Ziadia et al [10] also observed that winter conditions reduce pedestrian and distant vehicles' detection rate. Chebrolu et al [11] have mentioned that most models fail to predict pedestrians in a dark environment.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It supports the dramatic impact of winter on object detection. Ziadia et al [10] also observed that winter conditions reduce pedestrian and distant vehicles' detection rate. Chebrolu et al [11] have mentioned that most models fail to predict pedestrians in a dark environment.…”
Section: Introductionmentioning
confidence: 96%
“…Ziadia et al. [10] also observed that winter conditions reduce pedestrian and distant vehicles' detection rate. Chebrolu et al.…”
Section: Introductionmentioning
confidence: 99%